Chrześcijańska perspektywa rozwiązywania kwestii społeczno-ekonomicznych w świetle nauczania Jana Pawła II i założeń personalizmu G.M. Gronbachera - Twardowski, ks. Mirosław (Annales. Etyka w Życiu Gospodarczym, 2015)
In this essay I would like to outline the Christian perspective on solving economic issues based on documents of the Catholic Church. The term ‘economic personalism’ appeared in literature several years ago and has been used as a proposal of a new economic model which is supposed to be a synthesis of achievements of economic sciences and Christian moral theology. Pope John Paul II is believed to be one of its precursors or even founding-fathers. We shall sum up these significant elements of papal personalism under the following heads: (1) A man is a person, namely an independent existence in material and personal, spiritual and material sense, rational and free. All these characteristics of a human being constitute a basis for his dignity and greatness; (2) A man is a free being. This means that he has to make choices between various values. Human freedom is closely related to the truth. The final objective of human freedom is love; (3) We can protect ourselves against alienation by acting and being together with others. We will avoid the danger of alienation when we make ourselves a gift for the other person and especially for God. Economic personalism develops John Paul II’s personalistic view in a creative way. Its program can be summarized by the following theses: (1) a man is the centre of economy; (2) a human being is the most important economic good; (3) work is part of the man’s calling; (4) reproducibility of goods is subordinated to the man’s integral development; (5) the right to participate constitutes inalienable human right; (6) the principle of subsidiary is an „intellectual” frame for social and economic order; (7) the market should not be absolutized; (8) solidarity with the poor and social justice constitute a basis of each economy.